Laser-assisted oxidative polymerization of 3-octylthiophene (3OT) and its characterization. (March 2019) - Luna Mejía, N.L.; Alvarado-Tenorio, G.; Márquez Aguilar, P.A.; Nicho, M.E.; Calva-Yáñez, J.C.; Fuentes-Pérez, M.; Nava, R.; Escobar, S.
Graphical abstract: Highlights: We polymerize 3-octilthiophene by green laser-assisted by firts time. The irradiation favors the growth of low molecular weight fractions during the polymerization reaction. The band gap of P3OT films were slightly lower in comparison to reference one. Abstract: Regioramdom poly(3-octylthiophene) (P3OT) was successfully synthesized by laser assisted oxidative polymerization of 3-octylthiphene monomer. The polymerization reaction mixture was irradiated using a 532-nm laser source at different output power, from 0.5 W to 3 W. Results indicate that laser irradiation favors the growth of low molecular weight fractions during the polymerization reaction, promoting changes in the morphology and crystal size, with a significant reduction in process duration, from 24 h to 10 min. This polymerization route could have important industrial applications in optolectronic devices due to the widening of absorption spectrum and short synthesis time.